Pengaruh Pemasangan Solar Cell Terhadap Biaya pada Industri PT. Kahatex - Haz, Fauzia; Astif Syarifuddin, Shilham; Angga Setia, Giri (ELECTRON Jurnal Ilmiah Teknik Elektro, 2022)
This study uses data collection methods to compare how effective the use of solar cells is and the data is based on 2 parameters as reference material, namely real data with simulation data where real data obtained from solar cells in PT. KAHATEX while simulating using Pvsyst software, so it can be seen that the use of solar cells is more impactful as a substitute for conventional energy sources. From this data, it can also be calculated how much the costs have been cut and the impact given by the use of solar cells. After the analysis carried out, it was obtained data that each solar cell module produced an average of 1.32 kWh and also obtained data on the cost of electricity usage which was cut by an average of 4.8% of the total electricity demand from one Garment department at PT. KAHATEX. The installation of solar cells in one Garment Department saves electricity in the last 3 months, which is Rp. 31,006,265. The simulation results using Pvsyst software to expand the use of solar cells in the embroidery department showed that 297 units of modules are needed and the average in one module generates electricity of 1.18 kWh.